Predict the incidence of Guillain Barré Syndrome and arbovirus infection in Mexico, 2014-2019 - Lumumba Arriaga-Nieto; Porfirio Felipe Hernández-Bautista; Alfonso Vallejos-Parás; Concepción Grajales-Muñiz; Teresita Rojas-Mendoza; David Alejandro Cabrera-Gaytán; Israel Grijalva-Otero; Bernardo Cacho-Díaz; Leticia Jaimes-Betancourt; Rosario Padilla-Velazquez; Gabriel Valle-Alvarado; Yadira Perez-Andrade; et al. (Public Library of Science (PLoS), 2022)
The Dengue (DENV), Zika (ZIKV), and Chikungunya (CHIKV) virus infections have been linked to Guillain-Barré syndrome (GBS). GBS has an estimated lethality of 4% to 8%, even with effective treatment. Mexico is considered a hyperendemic country for DENV due to the circulation of four serotypes, and the ZIKV and CHIKV viruses have also been circulating in the country. The objective of this study was to predict the number of GBS cases in relation to the cumulative incidence of ZIKV / DENV / CHIKV in Mexico from 2014 to 2019. A six-year time series ecological study was carried out from GBS cases registered in the Acute Flaccid Paralysis (AFP) Epidemiological Surveillance System (ESS), and DENV, ZIKV and CHIKV estimated cases from cases registered in the epidemiological vector-borne diseases surveillance system. The results shows that the incidence of GBS in Mexico is positively correlated with DENV and ZIKV. For every 1,000 estimated DENV cases, 1.45 GBS cases occurred on average, and for every 1,000 estimated ZIKV cases, 1.93 GBS cases occurred on average. A negative correlation between GBS and CHIKV estimated cases was found. The increase in the incidence of GBS cases in Mexico can be predicted by observing DENV and ZIKV cases through the epidemiological surveillance systems. These results can be useful in public health by providing the opportunity to improve capacities for the prevention of arbovirus diseases and for the timely procurement of supplies for the treatment of GBS.